Working in the COVID-19 pandemic: an observational study - Lisbôa, Diego; Rocha, Thayssa da; Machado, Letícia; Caldeira, Clara; de Souza, Cleidson (Journal on Interactive Systems, 2021)
The restrictions of social isolation adopted to contain the spread of the COVID-19 pandemic have led many companies to adopt remote work in a mandatory and unplanned way. This sudden transition has caused profound changes in personal and professional relationships. In this article, we present the results of a qualitative observational study on the adaptations made in the activities of the software development process of two companies. These adaptations were intended to support the transition to teleworking during the pandemic. They were analyzed based on the theoretical framework of Olson and Olson for distributed collaboration. Software developers’ motivations and observed challenges are also presented. Based on these results, the article presents recommendations to facilitate the adaptation to remote work in software development teams.